Psychological Well-being of Students with Disabilities in an Inclusive Blended Learning Environment - Odintsova, M.; Kulyatskaya, M.G. (Psihologo-pedagogičeskie issledovaniâ, 2019)
The inclusive mixed learning environment is considered as a multifaceted, affordable and flexible system that effectively combines distance and traditional technologies and provides psychological well-being and personality development for all students, regardless of whether they have certain restrictions or not. The article showed the psychological well-being of students with disabilities is determined by environmental (macro factors); socio-psychological (mesofactors); personal characteristics of students, their ability to overcome difficulties (microfactors). It was established that the various components of psychological well-being and students' coping strategies have different significance depending on the specifics of university educational environment. The ability to master various types of activities, effectiveness in coping with difficulties (environmental management) is typical for students of two groups of an inclusive mixad learning environment. Life goals are more shaped in healthy students in an inclusive mixed learning environment. An inclusive environment has been found to be favorable for healthy and disabled students, who, in terms of their psychological well-being, do not differ from healthy students of traditional learning environment and use less constructive coping strategies to a lesser degree. Particular attention should be paid to such characteristic of psychological well-being of students with disabilities as self-acceptance, which distinguishes them from healthy students of the two groups. Инклюзивная среда смешанного обучения рассматривается как многогранная, доступная и гибкая система, эффективно сочетающая дистанционные и традиционные технологии и обеспечивающая психологическое благополучие и развитие личности всех обучающихся, вне зависимости от наличия у них тех или иных ограничений. Показано, что психологическое благополучие студентов с инвалидностью определяется множеством факторов: средовыми (макрофакторами); социально-психологическими (мезофакторами); личностными особенностями студентов, их способностями к преодолению трудностей (микрофакторами). Установлено, что разнообразные компоненты психологического благополучия и стратегии преодоления студентов имеют разную значимость в зависимости от специфики образовательной среды вуза. Способность к усвоению различных видов деятельности, эффективность в преодолении трудностей (управление средой) характерны для студентов двух групп инклюзивной среды смешанного обучения. Цели в жизни в большей степени сформированы у здоровых студентов инклюзивной среды смешанного обучения. Инклюзивная среда оказалась благоприятной для здоровых студентов и обучающихся с инвалидностью, последние из них по уровню психологического благополучия не отличаются от здоровых студентов традиционного обучения и в меньшей степени используют неконструктивные стратегии преодоления трудностей. Особое внимание педагогам и психологам стоит уделить такой характеристике психологического благополучия студентов с инвалидностью, как самопринятие, которая не лучшим образом отличает их от здоровых студентов двух групп.